Early Study on Visible (Vis) and Short-Wave Infrared (SWIR) Spectroscopy for Assessing Water Content in Olive Fruits: Towards Sustainable Land and Agricultural Practices - Giuseppe Bonifazi; Riccardo Gasbarrone; Davide Gattabria; Eugenio Lendaro; Luciana Mosca; Roberto Mattioli; Silvia Serranti (Land)
Accurate and rapid assessment of the water content in olive fruits is critical for enhancing the efficiency and sustainability of olive oil production. This study investigates the application of visible and short-wave infrared (Vis-SWIR) spectroscopy as a non-invasive method to directly measure the water content in intact olive fruits before milling, also affecting eco-friendly farming practices. Partial least squares (PLS) regression models for the olive fruit weight, weight loss, and water content were developed while using the dehydration process in a drying oven as the reference analysis. The models demonstrated strong predictive performance, with the PLS model for the olive fruit weight achieving a coefficient of determination in cross-validation (R2CV) of 0.78 and a root mean squared error (RMSECV) of 0.6 g. Additionally, for olive fruit weight loss, a R2CV of 0.96 with an RMSECV of 4.5% was achieved. Meanwhile, for the olive fruit water content, an R2CV of 0.94 with an RMSECV of 0.245 mL was obtained. The PLS regression model set up to predict the water content for intact olive fruits showed promise, as evidenced by its fit, RMSE in prediction, and residual prediction deviation (RPD) values (R2P = 0.80, RMSEP = 0.556 mL, and RPD = 2.247). The obtained results indicate that portable Vis-SWIR spectrophotometers provide a rapid and efficient alternative to conventional drying and weighing methods, facilitating early detection of olive fruit quality. This technological approach not only enhances the financial returns for producers but also supports sustainable agricultural practices. The use of Vis-SWIR spectroscopy has broader potential applications in the olive industry, including quality control, monitoring the water status of olive orchards, and optimizing irrigation management, contributing to the sustainable management of land and agricultural resources.